A factor market distortion research based on enterprise innovation efficiency of economic kinetic energy conversion. (April 2021) - Xiaoyang, Jia; Sheng, Lin
Abstract: Technological progress is the power and source of a country's economic growth, and it is also an embodiment of the quality of economic development. And enterprise innovation efficiency is one of the most important ways of technological progress. The transformation of economic kinetic energy, as a way of policy orientation, has an important impact on the improvement of enterprise innovation efficiency. In this paper, provincial panel data from 2000 to 2018 are selected to empirically test the effect of factor market distortion on enterprise innovation efficiency during the transformation of economic kinetic energy. Furthermore, FDI and technological spillover effect of patent application have certain relevancy with factor price distortion so we investigate the influence of factor price distortion and tested a discriminating effect of factor price distortion by means of OLS, 2SLS, GMM and other methods on FDI, import trade, patent application, and enterprise innovation efficiency effect. The results show that the technology spillover effects of the three channels of import trade, foreign direct investment and patent application show different characteristics at different stages of the distortion of factor market and the price distortion of capital and labor factor are used in technology spillover effect. In the original stage (2000–2008), local governments pursued the speed of economic development, distorted the factor market, caused resource misallocation, and then weakened and restrained the innovation efficiency effect of enterprises. The efficiency has been achieved through the technology spillover model. In the period after the transformation of economic momentum (2009–2018), the government paid more attention to the quality of economic development, the distortion degree of factor market was significantly reduced, the role of market mechanism was fully played, and the efficiency effect of enterprise innovation was gradually revealed.